Discriminatorybnb: A Discussion of Airbnb’s Race Problem, Its New Anti-Discrimination Policies, and the Need for External Regulation - Jason McCloskey (Washington University Journal of Law & Policy, 2018)
In this note, Jason McCloskey examines the issue of discrimination in the peer-to-peer short-term rental marketplace. Specifically, McCloskey examines Airbnb’s struggles with discrimination and the implementation of its new anti-discrimination policy. While it is yet to be seen whether the new policy is anything more than a hollow public relations move, McCloskey argues that more must be done to combat discrimination in Airbnb’s rental market. To hold Airbnb to its promise to be more inclusive, McCloskey argues that legislation at both the federal and state level that holds Airbnb liable for the action of its hosts is needed. Additionally, such liability can be created through a clarification of Title II of the Civil Rights Act of 1964. And finally, McCloskey argues that the emergence of competitors like Innclusive may push the market to self-regulate.
Keywords: Airbnb; peer-to-peer; discrimination; Civil Rights Act; legislation; Multiple Dwelling Law; lodging; inclusion; race; #airbnbwhileblack